EFEKTIVITAS MODEL TGT DALAM MENINGKATKAN AKTIVITAS DAN PENGUASAAN MATERI - Lamudin Lamudin; Arwin Achmad; Rini Rita T. Marpaung (Universitas Lampung, 2013)
The purpose of this study was to determine effectivity of using TGT model to increase activity and mastery of the human circulatory system. The design used was a pretest-posttest non-equivalent. The samples were students of XI IPA 1 and XI IPA 2 taken by cluster random sampling. Qualitative data taken from student activity and responses using TGT. Quantitative data obtained from the average value of the pretest, posttest and N-gain. The results showed all aspects of student learning activities increase (49.96%). Mastery of the material also increased in pretest (30%), posttest (71%) and N -Gain (59%). Students also give positive responses. Based on the results obtained from this study that: (1) The use of cooperative learning model type TGT effective in increasing student activity and mastery of the material in the human circulatory system, class XI Science High School N 13 Bandar Lampung, (2) The use of cooperative learning model types TGT able to increase the students activities in the subject matter of the human circulatory system, (3) Most of the students gave a positive response of using cooperative learning model type TGT on the subject matter in the human circulatory system. Keywords: human circulatory system, learning activities, TGT models.